1997
DOI: 10.1097/00128360-199704000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma in Situ of the Uterine Cervix: Management and Outcome

Abstract: As other institutions have reported [4], we have been enObjective: To retrospectively review the management of adeno-countering patients with cervical adenocarcinoma in situ carcinoma in situ of the uterine cervix, to determine the outcome with increasing frequency. The aim of the present study was of conization versus hysterectomy, and to compare the results to retrospectively review the Cleveland Clinic Foundation's achieved by different methods of conization. Methods: We per-clinical and pathologic experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 0 publications
1
37
0
3
Order By: Relevance
“…4,8,[13][14][15][16][17][18][19][20][21] Most authors believe that a patient with AIS does not require a second cone biopsy or hysterectomy if the margins are free of AIS in the initial cone biopsy specimen. The results of our study generally support this recommendation but they also highlight the context in which the recommendation needs to be made.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,[13][14][15][16][17][18][19][20][21] Most authors believe that a patient with AIS does not require a second cone biopsy or hysterectomy if the margins are free of AIS in the initial cone biopsy specimen. The results of our study generally support this recommendation but they also highlight the context in which the recommendation needs to be made.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, cold knife conization, with its higher risk of morbidity, is preferred to large loop excision of the transformation zone (LLETZ), as LLETZ has resulted in greater interfering artifact and higher rates of positive margins and recurrence of adenocarcinoma in situ (AIS). 10,11 Since the ThinPrep Pap Test (TPPT) (Cytyc Corporation, Boxborough, Massachusetts, U.S.A.) was approved as a replacement for the CPS in May 1996, a number of studies have reported significantly increased detection of both low and high grade squamous intraepithelial lesions. [12][13][14][15][16] There were fewer studies comparing TPPT to CPS with regard to performance with glandular lesions [17][18][19][20] and only one study specifically comparing the cytologic diagnosis of AGUS-EC.…”
mentioning
confidence: 99%
“…According to the 2001 Consensus Guidelines for the Management of Women with Cervical Cytological Abnormalities, 24 nearly half the patients with biopsy-confirmed AIS have a coexisting squamous abnormality and, therefore, the presence of a coexisting squamous abnormality does not change the management of women with AGC or AIS. 21,[24][25][26] AGC is a significant indicator of more serious lesions, such as high-grade preinvasive squamous disease, AIS, and invasive adenocarcinoma. [1][2][3][8][9][10][11][12][13][14][15][16] This case illustrates that AGC found upon Pap smear during a pregnancy can be associated with significant pathology for which an aggressive management approach is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of positive margins or recurrence for cervical AIS is significantly less when a cold knife conization is performed as opposed to a large loop excision of the transformation zone. 21 A narrow cone incorporating the entire endocervical canal (2.0 cm to 2.5 cm) should be carefully performed to avoid disrupting the endometrium or fetal membranes. 1,9,12,14,16,33,34 For conization under either spinal or general anesthesia, tocolytic therapy with nonsteroidal anti-inflammatory agents should be used to prevent contractions.…”
Section: Discussionmentioning
confidence: 99%